IMPROVEMENT OF BREEDING AND PRODUCTIVE TRAITS OF KALMYK CATTLE BREED - Baimukanov Dastanbek Asylbekovich,; Pristupa Vasily Nikolaevich,; Kolosov Yury Anatolevich,; Donnik Irina Mikhailovna,; Torosyan D. S.,; Kolosov Anatoly Yuryevich,; Orlova Olga Nikolaevna,; Yuldashbayev Yusupzhan Artykovich,; Chylbak-ool Salbak Olegovna, (Scientific Journal of Pedagogy and Economics, 2019)
The article analyzes the state of Rostov type of the Kalmyk cattle breed on the main biological and productive features; it was studied the economic and breeding traits of livestock in various production systems. During the research, indicators of the formation of meat productivity of the newly created factory lines with different keeping technologies were established. New data on the index assessment of the genotype of servicing bulls by the phenotype of sons and daughters, as well as by the manifestation of the productive traits of the young stock, new type of Kalmyk cattle, depending on the origin and growing intensity in the preweaning and post-weaning periodswere obtained. The research results serve as an important theoretical substantiation making a certain contribution to zootechnic science in order to improve the domestic livestock of meat productivity and can be used in practical work in the production of heavy carcasses and high-quality beef. This will increase the efficiency of the industry maintenance in a market economy and provide a more complete use of the productive capacity of the breed.